2007
DOI: 10.2519/jospt.2007.2539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in Posterior Tibialis Muscle Length Between Subjects With Posterior Tibial Tendon Dysfunction and Healthy Controls During Walking

Abstract: The greater PTLength, as determined from foot kinematics, suggests that the PT musculotendon is lengthened in subjects with stage II PTTD, compared to healthy controls. The amount of lengthening is not dependent on the phase of gait; however, different foot kinematics contribute to PTLength across the stance phase. Targeting these foot kinematics may limit lengthening of the PT musculotendon. Subjects with excessive PT lengthening experience a decrease in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
1
40
0
1
Order By: Relevance
“…However, these authors did not measure AHI, so comparisons are difficult. Both Neville et al 24 and Houck et al [8][9][10] measured AHI in individuals with stage II PTTD and found significantly lower values than in healthy controls. Therefore, the results of the current study suggest that arch structure, while perhaps not a contributing factor in stage I PTTD, may be more apparent in later stages of the condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these authors did not measure AHI, so comparisons are difficult. Both Neville et al 24 and Houck et al [8][9][10] measured AHI in individuals with stage II PTTD and found significantly lower values than in healthy controls. Therefore, the results of the current study suggest that arch structure, while perhaps not a contributing factor in stage I PTTD, may be more apparent in later stages of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…5,34 In contrast, individuals in the more severe stages of the PTTD progression generally exhibit marked differences in arch height, strength, and gait kinematics. 20,24 Several limitations are acknowledged. First, this study did not include the classically defined PTTD demographic of sedentary women over the age of 40, who are diabetic or obese.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prolonged pronation likely overloads the posterior tibialis tendon, resulting in localized degenerative changes, impaired muscle strength capacity, and pain. In the presence of flatfoot deformity, the result is typically increased hindfoot eversion, 16,17 increased transverse plane foot motion, 28,29,38 inefficient propulsion during locomotion, 32 and diminished plantar flexion moment. 28,32 The actions of the hip extensors and abductors are essential during walking.…”
Section: Women With Posterior Tibial Tendon Dysfunction Have Diminishmentioning
confidence: 99%
“…25,29 There is no doubt that acquired flatfoot deformity is accompanied by some level of tibialis posterior tendon dysfunction. The tibialis posterior functions to create a rigid foot segment by stabilizing the midfoot 37 and assists in generating energy, by the plantar flexors in terminal stance, to produce successful propulsion.…”
mentioning
confidence: 99%
“…Stage 1 AAFD is marked by pain and swelling along the posterior tibial tendon, without foot deformity. 4,6 Stage 2 AAFD is characterized by degeneration and elongation of the posterior tibial tendon, as well as flexible flatfoot deformity, 8,20,23 including damage to the midfoot joint capsules (eg, talonavicular and naviculocuneiform) and associated ligaments (eg, spring ligament). 7 Operative care is typically indicated at stage 3, when the flatfoot deformity becomes fixed, and at stage 4, when deformity progresses to the ankle joint.…”
mentioning
confidence: 99%